Como atingir a interação, visando à construção do conhecimento e à aprendizagem de língua portuguesa, em ambientes virtuais - Reis, Renata Cristina dos (2009)
Study on interaction, in distance education of Portuguese Language, carried out in a semi-presence university course. The inquiry started from the following question: How to reach the interaction, aiming at the construction of knowledge and the learning of Portuguese, in virtual environments? In the search for the answer, the objective was to analyze the development of the possible strategies of interaction in the virtual environment of education and learning of Portuguese, in a collective perspective, using the subject "Comunicação e Expressão" to verify the interaction between the participants and the role of the teacher as the mediator of this process. The course was hosted in Moodle Platform, and the research was based on the relations between interaction, mediation and collaborative work, agreeing with Masetto's proposal for the use of specific pedagogical mediation strategies (2003) and (1999), as well as the possibilities of mediation proposed by Belloni (2006) and also Valente's view of virtual environments in a "virtual togetherness" perspective (2004). In a qualitative basis, the analyses were carried out based on textual dialogues that happened with the use of the following tools: E-mail, Discussion and Activities Forum and Chats. The conclusion was that the interventions of the tutor made the course become dynamic, with gradual evolution in collaborative work. The analyses showed that this dynamism enabled the re (elaboration) of concepts from the linking of individual solutions (self-learning) with group discussion (inter-learning)